2010
DOI: 10.1007/s10329-010-0230-6
|View full text |Cite
|
Sign up to set email alerts
|

The anthropogenic environment lessens the intensity and prevalence of gastrointestinal parasites in Balinese long-tailed macaques (Macaca fascicularis)

Abstract: The distribution of wildlife parasites in a landscape is intimately tied to the spatial distribution of hosts. In parasite species, including many gastrointestinal parasites, with obligate or common environmental life stages, the dynamics of the parasite can also be strongly affected by geophysical components of the environment. This is especially salient in host species, for example humans and macaques, which thrive across a wide variety of habitat types and quality and so are exposed to a wealth of environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 61 publications
3
62
0
Order By: Relevance
“…Studies have shown that Giardia sp. infections increase with increasing contact with humans and livestock across multiple wild primate species (Johnston et al 2010;Kowalewski et al 2011;Lane et al 2011). Interestingly, four out of five host speciesbarking deer, sambar, Indian porcupine and Asian elephantthat were found to be infected with Giardia sp.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have shown that Giardia sp. infections increase with increasing contact with humans and livestock across multiple wild primate species (Johnston et al 2010;Kowalewski et al 2011;Lane et al 2011). Interestingly, four out of five host speciesbarking deer, sambar, Indian porcupine and Asian elephantthat were found to be infected with Giardia sp.…”
Section: Discussionmentioning
confidence: 97%
“…Of the seven species of Giardia sp., G. intestinalis is known to infect humans, cattle, dogs and cats, and cause gastrointestinal distress. However, species like G. muris is host specific and transmission to humans is rather rare (Johnston et al 2010;Lane et al 2011). Studies have shown that Giardia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, our ability to predict specific disease outcomes of such changes remains poor Chapman et al 2009b). The growing body of literature addressing potential impacts of anthropogenic disturbance on the relationship between primates and their parasites is clear indication that the primatological community is taking this problem seriously (Hahn et al 2003;Chapman et al 2005;Gillespie et al 2005;Chapman et al 2006;Weyher et al 2006;Trejo-Macias et al 2007;Gillespie & Chapman 2008;Mbora & McPeek 2009;Lane et al 2011). However, truly understanding the potential impacts of anthropogenic disturbance on these relationships, or the impacts of specific parasitic organisms on their primate hosts for that matter, requires investigation of baseline epidemiological factors that naturally contribute to infection dynamics .…”
Section: Primate Disease In Perspectivementioning
confidence: 99%
“…McLennan et al 2017). However, with the exception of Lane et al’s (2011) study on Macaca fascicularis , few primate studies include highly human-populated urban areas. Furthermore, the majority of anthropogenic parasite studies focus on comparisons between only two study sites.…”
mentioning
confidence: 99%